Possibility of environmentally-safe casing soil disinfection for control of cobweb disease of button mushroom - Potočnik, Ivana S; Rekanović, Emil; Stepanović, Miloš; Milijašević-Marčić, Svetlana; Todorović, Biljana; Nikolić-Bujanović, Ljiljana; Čekerevac, Milan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
The soil-borne pathogen Cladobotryum dendroides causes cobweb disease of button mushroom (Agaricus bisporus) and its significant yield losses. Casing soil disinfection by toxic formaldehyde is a widespread practice. The aim of this study was to investigate the potential of two environmentally friendly substances, colloidal silver and peracetic acid, against C. dendroides. Their biological efficacy (impact on mushroom yield), effectiveness (disease control) and type of interactions between them and the fungicide prochloraz-manganese were evaluated.Black peat/lime casing soil was applied to a colonized substrate with the white button mushroom strain 737, then inoculated with C. dendroides and treated with the fungicide prochloraz-manganse and two environmentally friendly disinfectants based on peracetic acid and colloidal silver. The effects of fungicides on mushroom productivity were evaluated as biological efficacy and calculated as a ratio of fresh weight of total mushroom yield to the weight of dry substrate. Fungicide effectiveness and synergy factor were calculated by Abbott’s (1925) formula. Tests for synergism between prochloraz-manganese and both other substances were performed using Limpel’s formula.The highest biolgical efficacy, exceeding 92.00, was achieved in treatments with prochloraz-manganese, applied alone or in combination with both other disinfectants. The highest effectiveness of 93.33% was attained in treatments with peracetic acid combined with prochloraz-manganese. Trials against cobweb disease revealed a synergistic reaction between the fungicide and peracetic acid and antagonistic between the fungicide and colloidal silver.Peracetic acid provided better disease control, compared to colloidal silver applied alone or in combination with the fungicide. Based on these findings, peracetic acid should be recomended as an environmentally friendly casing soil disinfectant against cobweb disease of A. bisporus.
Keywords: Soil disinfection; Colloidal silver; Peracetic acid; Prochloraz; Cladobotryum dendroides; Agaricus bisporus